2017
DOI: 10.1038/s41598-017-15491-6
|View full text |Cite
|
Sign up to set email alerts
|

A non-smooth tumor margin on preoperative imaging assesses microvascular invasion of hepatocellular carcinoma: A systematic review and meta-analysis

Abstract: Microvascular invasion (MVI) is rarely diagnosed preoperatively in hepatocellular carcinoma (HCC). The aim of this meta-analysis is to assess the diagnostic power of a non-smooth tumor margin on preoperative imaging for MVI. We performed a literature search using the PubMed, Embase and Cochrane Library databases, and 11 studies were included involving 618 MVI-positive cases and 1030 MVI-negative cases. Considerable heterogeneity was found, and was indicated to be attributable to the mean patient ages in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 30 publications
6
60
0
Order By: Relevance
“…Shape-related characteristics were adopted to express the complexity of the lesion shape. Given histological studies, MVI-positive HCC exhibited an aggressive tendency, invading the tumor envelope and extending into the noncancerous substance, thereby causing a higher incidence of irregular tumor margins [ 23 ]. Matrix-based characteristics are second-order statistics applied to express lesions complex characteristics, the variation of hierarchical structure, and the thickness of texture.…”
Section: Discussionmentioning
confidence: 99%
“…Shape-related characteristics were adopted to express the complexity of the lesion shape. Given histological studies, MVI-positive HCC exhibited an aggressive tendency, invading the tumor envelope and extending into the noncancerous substance, thereby causing a higher incidence of irregular tumor margins [ 23 ]. Matrix-based characteristics are second-order statistics applied to express lesions complex characteristics, the variation of hierarchical structure, and the thickness of texture.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a non‐smooth tumor margin on preoperative imaging revealed to have great value for MVI assessment according to a systematic review 16 . A treatment strategy for a non‐smooth tumor margin of HCC is required because sectionectomy or larger hepatectomy or adjuvant therapy such as TACE after hepatectomy has been reported to improve survival for patients with HCC and MVI.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, HB‐phase images on Gd‐EOB‐DTPA‐enhanced MRI (EOB‐MRI) predict the MVI of HCC preoperatively. In detail, a non‐smooth tumor margin on HB‐phase images predicts MPVI or intrahepatic metastasis (IM) of HCC 10‐16 . If, on one hand, sectionectomy or larger hepatectomy has been recently reported to decrease the risk of intrahepatic recurrence of HCC and to improve overall survival (OS), on the other hand recurrence‐free survival (RFS) rates and OS rates have not been evaluated in relation to the tumor margin on EOB‐MRI 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al [31] reported that irregular tumor margin was alone independent predictive factor for MVI among previously proposed predicting factors such as fluorine-18 fluorodeoxyglucose-positron emission tomography (FDG-PET) results and serum tumor markers. Hu et al [32] demonstrated in a meta-analysis that CT is superior to MRI in evaluating an irregular tumor margin for MVI assessment. Banerjee et al [33] showed new features of contrast CT that can also accurately predict histological MVI in HCC surgical candidates.…”
Section: Prediction Of MVI Using Contrast Ctmentioning
confidence: 99%